2016
DOI: 10.1111/ggi.12876
|View full text |Cite
|
Sign up to set email alerts
|

Height is an indicator of vascular maintenance capacity in older men

Abstract: Height positively correlates with circulating CD34-positive cells in systolic, but not non-systolic, hypertensive men. As the beneficial effects of circulating CD34-positive cells on endothelial repair might be masked by hypertension where the production of CD34-positive cells is stimulated by hypertension-induced vascular damage, among individuals with systolic hypertension, circulating CD34-positive cells should indicate the limits of endothelial repair. Therefore, height might indicate the capacity for adeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…In previous study, a significant positive correlation was reported between height and number of circulating CD34-positve cells in subjects with systolic hypertension but not in those without, independent of known cardiovascular risk factors [ 28 ]. And we also reported in previous study that the number of platelets and circulating CD34-positive cells acts as an indicator of the activity of the vicious cycle that exists between hypertension and endothelial dysfunction in elderly Japanese men [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous study, a significant positive correlation was reported between height and number of circulating CD34-positve cells in subjects with systolic hypertension but not in those without, independent of known cardiovascular risk factors [ 28 ]. And we also reported in previous study that the number of platelets and circulating CD34-positive cells acts as an indicator of the activity of the vicious cycle that exists between hypertension and endothelial dysfunction in elderly Japanese men [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that height indicates the capacity of vascular repair in elderly men with hypertension [14]. We also reported a significant positive association between hemoglobin and hypertension [15], hypertension-induced vascular damage [16], and atherosclerosis [17].…”
Section: Introductionmentioning
confidence: 96%
“…In the present study, although the correlation between height and platelet count is small, short stature activates vascular remodeling more strongly than tall stature for following reasons. First, height is positively associated with vascular maintenance capacity [28]. If aggressive vascular repair is evoked by serious endothelial damage, the maximum ability of vascular repair should be defined by height-subjects with a short stature would not activate vascular repair as strongly as subjects with a tall stature (ceiling effect).…”
Section: Discussionmentioning
confidence: 99%
“…Because creatinine clearance data were not available and estimated glomerular filtration rate (GFR) is not an effective tool for evaluating kidney function for a comparison of associations with various body heights [1,2,5,27,28, 32], we were not able to perform an analysis adjusted for exact renal function. However, our study showed that the association between height and platelet count remained significant even after adjustment for serum creatinine.…”
Section: Discussionmentioning
confidence: 99%